2021
DOI: 10.1021/jasms.0c00427
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Small Molecule Isomeric Glucuronide Metabolite Differentiation Using In Silico and Experimental Collision Cross-Section Values

Abstract: Identifying isomeric metabolites remains a challenging and time-consuming process with both sensitivity and unambiguous structural assignment typically only achieved through the combined use of LC–MS and NMR. Ion mobility mass spectrometry (IMMS) has the potential to produce timely and accurate data using a single technique to identify drug metabolites, including isomers, without the requirement for in-depth interpretation (cf. MS/MS data) using an automated computational pipeline by comparison of experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…However, CCS prediction tools cannot be used to confirm the identification of an unknown compound. Connolly and coworkers have shown that predicted CCS values cannot accurately describe the difference of CCS values for isomeric glucuronide pairs . Technological developments are on-going though, and as the accuracy and reproducibility of experimentally obtained CCS values improves, a similar improvement can be expected in the accuracy of predicted CCS values.…”
Section: Resultsmentioning
confidence: 99%
“…However, CCS prediction tools cannot be used to confirm the identification of an unknown compound. Connolly and coworkers have shown that predicted CCS values cannot accurately describe the difference of CCS values for isomeric glucuronide pairs . Technological developments are on-going though, and as the accuracy and reproducibility of experimentally obtained CCS values improves, a similar improvement can be expected in the accuracy of predicted CCS values.…”
Section: Resultsmentioning
confidence: 99%
“…Later, the same ML model was compared with QM approaches using MOBCAL on glucuronides. 177 As it turned out, the overall difference between the experimental TW CCS N2 and the predicted CCS using the ML approach was lower compared with the QM approach. More compounds with the ML approach were within a 2% difference (Figure 3).…”
Section: Metccs and Lipidccsmentioning
confidence: 93%
“…The web server for this model is accessible through CCSondemand (waters.com). Later, the same ML model was compared with QM approaches using MOBCAL on glucuronides 177 . As it turned out, the overall difference between the experimental TW CCS N2 and the predicted CCS using the ML approach was lower compared with the QM approach.…”
Section: Ccs Modelsmentioning
confidence: 99%
See 2 more Smart Citations